SOILS in India: Text book of soil science - P.C. Das; P.C. Das (Ludhiana Kalyani)
Soil science which is one of the important disciples of agicultural science.soil is regarded as 'mother'.Mother nourishes her children for their growth and development.
Soil formation soil air soil water soil fertility
Keywords: Soil formation , soil air, soil water